Asymmetric loan loss provision models - Basu, Sudipta; Vitanza, Justin; Wang, Wei (Journal of Accounting and Economics, 2020)
Large net loan charge-offs are frequently associated with large decreases in nonperforming loans and large increases in loan loss provisions, inducing a V-shaped relation between loan loss provisions and nonperforming loan changes. Failure to model the asymmetry attributable to net loan charge-offs can change inferences about the presence of earnings management and the effects of delayed loan loss recognition in prior papers that assumed linearity. Future researchers should either include net loan charge-offs in linear models of loan loss provisions or explicitly model the asymmetry induced by omitting net loan charge-offs.